Extracorporeal photopheresis as induction therapy in lung transplantation for cystic fibrosis: a pilot randomized trial - Righi, Ilaria; Fenizia, Claudio; Trabattoni, Daria; Nosotti, Mario; Grisorio, Giacomo; Vanetti, Claudia; di Tella, Sonia; Mocellin, Cristina; Fantini, Norma; Prati, Daniele; Morlacchi, Letizia Corinna; Rossetti, Valeria; et al. (Frontiers in Immunology, 2025)
IntroductionExtracorporeal photopheresis (ECP) is a viable treatment that slows the progression of chronic lung allograft dysfunction. Despite its immunoregulatory potential, data on extracorporeal photopheresis as an induction therapy remain rather limited.MethodsWe conducted a pilot randomized controlled study on ECP as induction therapy in cystic fibrosis patients undergoing primary lung transplantation. Primary endpoints included safety, assessed based on the incidence of adverse events, treatment-related toxicity, and procedure-related complication rates; and feasibility, evaluated through the completion rate of scheduled ECP sessions, patient tolerability, and treatment discontinuation rates. Secondary endpoint consisted of an exploratory assessment of efficacy, using a composite measure that included three key components: freedom from biopsy-proven acute rejection within the first 12 months, absence of chronic lung allograft dysfunction at 36 months, and optimal graft function, defined as a predicted forced expiratory volume in the first second ≥ 90% at 36 months. Finally, exploratory endpoints included cell phenotypic and functional analyses, secreted immune protein profiling, and gene expression analysis for mechanistic insights. Patients were randomly assigned to receive either standard immunosuppressive therapy alone or standard therapy plus six sessions of extracorporeal photopheresis, with a follow-up period of 36 months.ResultsAmong 36 cystic fibrosis patients who underwent lung transplantation between 2018 and 2021 and met the eligibility criteria, 21 were randomized (9 to the study group and 12 to the control group). No patients in the treatment group experienced adverse events. The enrollment rate was 61%, and the treatment discontinuation rate was 22%. The clinical composite endpoint was achieved by 28.6% of patients in the treatment group and 16.7% in the control group. Exploratory endpoint analyses revealed significant decreases in pro-inflammatory cytokines, degranulating CD8+ T lymphocytes, and NK cells in the treatment group. Moreover, significant increases in Treg lymphocytes, IL-10-producing NK cells, and anti-inflammatory cytokines appeared to be associated with improved pulmonary function in the treatment group.ConclusionsInduction therapy with extracorporeal photopheresis is safe and feasible in lung transplantation for cystic fibrosis. Some clinical benefits appear to persist for the first 36 months of follow-up. Interestingly, a correlation between immunological modulation induced by extracorporeal photopheresis and pulmonary function was observed.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT03500575?cond=NCT03500575&rank=1, identifier NCT03500575.